Optimization of tannin extraction from cavendish banana (Musa acuminata Colla) peel and production of its powder - Ishak, Nur Arnisah (2021)
Musa acuminata Colla (Cavendish) is one of the most abundant bananas in Malaysia that is highly exported and considered vital commercial crops in the region. The rejected bananas comprise about 20% of unripe that are collected as agricultural residues during the sorting process. These agricultural residues cannot be imported due to the multiple quality requirements such as shape abnormality and prematureness of size, which do not meet the commercial standards. As a result, these agricultural residues may create detrimental environmental issues in the long term if there are no alternative solutions. Banana peel is the primary residue corresponding to 40% of the fruit weight with a broad natural antioxidant such as polyphenols. The recovery of these compounds will be valuable to the food industry. This study aimed to turn unripe Cavendish peel into beneficial nutraceutical powders containing antioxidant-rich tannin. The present study began with the characterization of the physicochemical analyses, solvent selection for high extracted tannin content from the unripe and ripe peels and evaluated the thin-layer drying characteristic for unripe material. Next, the response surface methodology (RSM) was designed to optimize ultrasound-assisted extraction (UAE) process parameters for extracted tannin content by water as a solvent. The spray drying was used to optimize the operating parameters at different levels to encapsulate powder containing bioactive compounds and performed good properties. The potential bioactive compounds from the optimum water extract and spray-dried powder were quantified by HPLC analysis. The results showed that the total phenolic, tannin and flavonoid content from unripe Cavendish peel water extract was significantly higher (p < 0.05) than other solvents. Besides, a 40 ℃ drying condition was the best environment to dry the unripe peel as the extracted tannin content was significantly higher (p < 0.05) to be recovered than 50℃, 60℃ and 70℃. The UAE parameters were affected the yield recovery, total tannin and flavonoid content also antioxidant activities (DPPH and ABTS) significantly (p < 0.05). The optimum UAE extraction condition was at 60 ℃, an extraction time of 30.0 min, a 25.0 min for a pre-incubation time and a 5.03% solvent concentration as the recovery yield was 14.9% and 119.2 mg TAE/g sample of tannin content. It also contained a 29.0 mg RE/g sample of flavonoid, scavenging activities at 80.8% and 84.7% for DPPH and ABTS assays. Next, adding 7.09% maltodextrin concentration at 160 ℃ of inlet air temperature resulted in an optimum spray drying condition for unripe Cavendish peel powder. The response variables of powder recovery, moisture content, hygroscopicity, solubility, flowabilities (CI and HR), tannin and flavonoid content also antioxidant activities were fitted to the polynomial model significantly with a high coefficient of determination (R2 > 0.70) and insignificant lack of fitness (p > 0.05), thus give the best characteristics in the encapsulated powder. The unripe Cavendish peel powder showed good characteristics and appearance as a powder-formed with 1.89% moisture content, 30.81 mg water/100 g dry solid hygroscopicity, 55.60% solubility, 0.53 gcm-3 bulk density, 49.81% CI, 1.97 of HR flowability, 26.66 mg TAE/g powder of tannin content, 0.20 mg RE/g powder of flavonoid content, 78.99% DPPH and 72.17% ABTS of antioxidant activities. The HPLC quantification revealed tannic acid was detected as a lead compound with the highest quantity in both optimum conditions with 1551.210 ± 4.90 μg/g sample and 409.542 ± 4.31μg/g sample, respectively. It could be seen that the amount of tannic acid was quite remarkable in the HPLC profile. Therefore, the optimum UAE extraction and spray-dried processes were successfully obtained for antioxidantrich powder production from the unripe Cavendish peel. This product is a potential polyphenol source, especially the tannin content as a potent natural antioxidant with a stable formulation of spray-dried powder with strong reconstitution, lower water activity and is ideal for storage and used in the food industry for its antioxidants benefits.